Laparoscopic Approach to a Rare Cause of Ureteropelvic Junction Obstruction in a Child: Ureteral Polyp - Mehmet Surhan Arda; Huseyin Ilhan; Taylan Kara; Deniz Arık; Baran Tokar (Georg Thieme Verlag KG, 2015)
Abstract Fibroepithelial polyps are a rare underlying reason of ureteropelvic junction obstruction. In the past, open surgery was the only option. However, due to development of minimal invasive technics, treatment alternatives have been changed. Resection by laparoscopy or endoscopy, laser fulguration and/or percutaneous resection are recommended in children and adults. Here, we present a 10-year-old boy with severe left hydronephrosis due to fibroepithelial polyp close to the ureteropelvic junction and our laparoscopic approach.